Изменчивость Lagurus ovatus L. под влиянием диметилсульфата (ДМС) - Кудина, Г.А. (Промышленная ботаника, 2002)
The results of examining the effect of dimethylsulphate (DMS) upon the Lagurus ovatus seeds are expounded. It is determined, that the treatment of the seeds by 0,01% DMS with 6 and 18 hours’ exposure and by the concentration of 0,05% with the exposure of 6 hours stimulates seed germination, but does not effect leaf, panicle and generative shoots size. Seeds exposure to 0,005% concentration of DMS during 18 hours inhibits seed germination, but positively increases generative shoots height, panicle and leaf size, causes appearing of branchy forms. As a result of the research, hare’s tail grass forms perspective for the further selective work, have been singled out.